Environmental Impact of Online Versus in-Person Critical Care Education Through the Carbon Footprint Analysis of the CERTAIN Program: Cross-Sectional Study - Baiyong Wang; Claudia Castillo Zambrano; Nasrin Nikravangolsefid; Ricardo Machado Carvalhais; Alexander Niven; Ognjen Gajic; Yue Dong (JMIR Formative Research)
Abstract BackgroundClimate change is a pressing public health issue, with the US health care sector contributing about 479 million tons of carbon dioxide (CO22 ObjectiveThis study aimed to evaluate the carbon dioxide equivalent (CO2 MethodsA cross-sectional analysis of CO22 ResultsLocal courses had the highest emissions: 52.7 tons/course (2.5 tons/participant), 96% from air travel (50.6tons, PPP ConclusionsThe transition to online delivery of our CERTAIN global education program has led to a substantial reduction in CO2